(untitled) (Baghdad Science Journal, 2025)
A New Spectrophotometric Methods are improved for determination Metronidazole (MTZ) and Metronidazolebenzoate (MTZB) depending on1STand 2nd derivative spectrum of the two drugs by using ethanol as a solvent. Many techniques were proportionated with concentration (peak high to base line, peak to peak and peak area). The linearity of the methodsranged between(1-25µg.ml-1) is obtained. The results were precise and accurate throw RSD% were between (0.041-0.751%) and (0.0331-0.452%), Rec% values between (97.78, 101.87%) and (98.033-102.39%) while the LOD between (0.051-0.231 µg.ml-1) and (0.074-1.04 µg.ml-1) and LOQ between (0.170-0.770µg.ml-1) and (0.074-0.313 µg.ml-1) of (MTZ) and of (MTZB) respectively. These Methods were successfully applied to determination of (MTZ) and (MTZB) in the pharmaceutical preparatio; ns